MAKNA TARIAN SIALO PADA RITUAL RAMBU SOLO LUWU SULAWESI SELATAN - Harlin Palanta; Tony Tampake (Jurnal Ilmu Budaya, 2023)
This research discusses the meaning of sialo dance. Sialo dance is one of the traditions of the Bastem Luwu community in South Sulawesi which is performed at the death ceremony (rambu solo). Understanding the values and meanings contained in sialo dances is often neglected and lack of concern, including the millennial generation not understanding and not knowing the values and meanings of sialo dances contained therein. The focus of this research explores the meanings contained in the sialo dance at the rambu solo ceremony from the perspective of the sociology of local culture. this writing is useful to increase knowledge about the culture of Luwu South Sulawesi.The author uses qualitative method research realist ethnographic approach to describe the meanings of interaction and cultural values of sialo dance. The author's local cultural sociology study uses the perspective of Herbert Mead's thinking, Herbert Blumer, Clifford Geertz with the perspective of symbolic interactionism studies. The research location is Lalong Village, Luwu Regency, Walenrang District, South Sulawesi. This writing is focused on exploring the meanings and values of the sialo dance which is the local culture of the Bastem community at the rambu solo ceremony. The results of this study indicate the meaning of the sialo dance, which is meaningful to tell the life history of the deceased person who was celebrated. In addition, this dance also has a meaning to welcome government guests who come to share grief with the deceased family.